Women in menopause: the osteoporosis problem - Berrocal Kasay, Alfredo (2015)
Osteoporosis is a potential health problem in the postmenopausal period. It does not only decrease bone mass but also increases fracture risk and morbidity and mortality in these patients. Diagnosis is done by central bone densitometry (DXA) and treatment is non-pharmacologic and by various drugs that either inhibit osteoclasts (anti resorptives) or stimulate osteoblasts (anabolics). All patients must receive calcium and vitamin D. Drug election (either anti resorptive or anabolic) will depend on the patient presenting exclusive vertebral osteoporosis or also non-vertebral osteoporosis, or whether the patient develops clinical vertebral fractures.